Looking at the Silver Lining: The Success and Opportunity Stories of Students During the Pandemic Period (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
The COVID-19 pandemic has profoundly impacted education systems worldwide, forcing institutions to adapt to remote learning modalities. This study delves into the lived experiences of UCC students during this unprecedented period, uncovering the challenges and opportunities they encountered in navigating the online learning landscape.Adopting a qualitative approach, the study employed Husserlian Phenomenology to capture the essence of students' experiences. Nine participants were randomly selected through purposive sampling, ensuring a diverse representation of UCC students' backgrounds and perspectives. Data collection occurred in October 2022, utilizing semi-structured interviews to gather in-depth insights. Thematic analysis was employed to analyze the data, yielding three overarching themes: liabilities, assets, and profit.Liabilities: Navigating the Challenges of Online LearningThe transition to online learning brought myriad challenges for UCC students. The abrupt shift from face-to-face to virtual interactions disrupted established learning routines, posing significant obstacles for students accustomed to in-person instruction. Adapting to the new learning environment proved particularly difficult for those lacking access to reliable internet connectivity and adequate technological resources. Additionally, the pandemic’s economic impact placed financial strain on many families, exacerbating existing challenges and hindering students' ability to engage fully in online learning.Assets: Embracing the Advantages of Online LearningDespite the challenges, online learning presented several advantages for UCC students. The flexibility of virtual classes allowed students to manage their time more effectively, balancing academic pursuits with part-time employment or other commitments. This flexibility proved particularly beneficial for students with families or those residing in remote areas. Additionally, online learning platforms facilitated access to many educational resources, enabling students to supplement their studies with additional materials and engage with diverse perspectives.Profit: Turning Challenges into OpportunitiesIn response to the challenges of online learning, UCC students demonstrated remarkable resilience and adaptability. They devised innovative strategies to overcome obstacles, utilizing online resources and support networks to enhance their learning experience. Many students embraced the flexibility of online learning, pursuing entrepreneurial ventures, or engaging in volunteer activities alongside their studies. These experiences fostered personal growth and development, empowering students to acquire new skills and enhance their employability.Based on the study’s findings, the following recommendations are proposed:Institution-level Initiatives:• Establish partnerships with organizations offering part-time and full-time job coaching.• Provide instructor skill training, focusing on digital platforms and emerging technologies.Office of Students Affairs (OSAS) Initiatives:• Enhance career guidance programs, emphasizing problem-solving strategies for navigating the changing education landscape.• Collaborate with external agencies to expand student access to career development resources.UCC Students:• Actively explore opportunities and resources available to address their development needs.• Utilize support networks and mentorship programs to navigate challenges and enhance academic success.Future Research DirectionsFuture researchers could embark on the following: a. Investigating the long-term impact of online learning on UCC students' academic performance and career trajectories; b. They are exploring the experiences of marginalized student groups, such as those with disabilities or socio-economic disadvantages; and c. They are examining the role of institutional policies and practices in shaping students' online learning experiences.By delving deeper into these areas, researchers can gain a more comprehensive understanding of the opportunities and challenges UCC students face in the evolving landscape of online education.
Keywords: UCC Online learning; Challenges; Opportunities; Resilience; Adaptation